PELATIHAN PEMBUATAN FILM ANIMASI UNTUK MENINGKATKAN KREATIFITAS SISWA SMP AL IRSYAD KOTA SURAKARTA - Farida, Anisatul; Hasanah, Herliyani (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2024)
One measure of the effectiveness of the learning activity process is the inventiveness of the students. Pupils that demonstrate originality in their study will be acknowledged through a variety of methods. Enhancing students' creative storytelling skills during the learning process is the goal of this service project. Training in creating educational films with three-dimensional animation will be provided to service activity participants. This community service activity (PkM) applies the use of animated film making applications in learning at Al Irsyad Middle School. The PKM activity was attended by 14 class IX students of SMP Al Irsyad Surakarta. The implementation method used in this PkM activity is preparation, implementation, and evaluation. Training on how to make animated films using the Toontastic 3D application and direct practice in making animated films, as well as two-way discussions. Assistance for this training is through guidance to students via WhatsApp after the training takes place. The results of the activity evaluation in the form of a questionnaire regarding student motivation after participating in training in making learning media using animated films, showed that participants were very satisfied with an average score of 4.6 for the training activity. Students are able to practice how to make animated films themselves. That's why this training is said to be successful. This feedback shows satisfaction and provides participants with good enough motivation to participate in the training delivered. This service activity also provided a good response from partners.